2021
DOI: 10.3390/su13158431
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals in Early COVID-19 Prevention and Control

Abstract: Recent failures in COVID-19 prevention and control in some of the richest countries raise questions about the relevance of Sustainable Development Goals (SDGs) in the fight against pandemics. To examine this issue, we adopted the measure of countries’ progress for the SDGs in the SDG Index Scores (SDGS) and employed two analytical devices. The first was regression-aided adjustment of the number of deaths and confirmed cases. The second was the use of robust regressions to control the undue influence of outlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a qualitative study performed by Alibegovic et al ( 2020 ) to assess the impacts of COVID-19 on the SDGs in Italy, the following global goals were found to be the most impacted ones: SDG-1 (ending poverty), SDG-4 (education characterized by good quality and equitable), and SDG-8 (decent work and economic growth). As an outcome of their research on the adequacy of the SDGs to assess the readiness and resilience of countries facing global sustainability threats such as COVID-19 crisis, Kim and Kim ( 2021 ) concluded that countries with high SDG index scores were able to effectively control the catastrophic mortality from COVID-19, even though they were being unable to control the spread of infection. Accordingly, the impacts of COVID19 on the SDGs will vary in different communities, depending on the economic well-being, social structure, population density, resource availability, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a qualitative study performed by Alibegovic et al ( 2020 ) to assess the impacts of COVID-19 on the SDGs in Italy, the following global goals were found to be the most impacted ones: SDG-1 (ending poverty), SDG-4 (education characterized by good quality and equitable), and SDG-8 (decent work and economic growth). As an outcome of their research on the adequacy of the SDGs to assess the readiness and resilience of countries facing global sustainability threats such as COVID-19 crisis, Kim and Kim ( 2021 ) concluded that countries with high SDG index scores were able to effectively control the catastrophic mortality from COVID-19, even though they were being unable to control the spread of infection. Accordingly, the impacts of COVID19 on the SDGs will vary in different communities, depending on the economic well-being, social structure, population density, resource availability, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%